2019
DOI: 10.1155/2019/4569707
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Validation of an Analytical Method for Lincomycin Determination in Feathers and Edible Tissues of Broiler Chickens by Liquid Chromatography Tandem Mass Spectrometry

Abstract: Recent studies have detected different antimicrobial residues in broiler chicken feathers, where they persisted for longer periods of time and at greater concentrations than in edible tissues. However, until today, lincomycin behaviour in this nonedible tissue has not been assessed yet. Considering this, an analytical methodology to detect and quantify this antibiotic concentration in feathers, muscle, and liver tissues from broiler chickens was implemented and in-house validated. The methodology will allow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…LOD was estimated in range 0.2-0.5 µg/kg and recovery range 82.1-101.4% with relative standard deviation (RSD) <11.1% [3]. Maddaleno et al [4] reported the LOD was 19, 22, and 10 µg/kg and limit of quantification was 62, 73, and 34 µg/kg in feather, muscle, and liver, respectively. Recovery levels reported between 98 and 101% and calibration curve (r²) reported >0.99.…”
Section: Lc-msmentioning
confidence: 99%
See 2 more Smart Citations
“…LOD was estimated in range 0.2-0.5 µg/kg and recovery range 82.1-101.4% with relative standard deviation (RSD) <11.1% [3]. Maddaleno et al [4] reported the LOD was 19, 22, and 10 µg/kg and limit of quantification was 62, 73, and 34 µg/kg in feather, muscle, and liver, respectively. Recovery levels reported between 98 and 101% and calibration curve (r²) reported >0.99.…”
Section: Lc-msmentioning
confidence: 99%
“…Maddaleno et al . [ 4 ] reported the LOD was 19, 22, and 10 μg/kg and limit of quantification was 62, 73, and 34 μg/kg in feather, muscle, and liver, respectively. Recovery levels reported between 98 and 101% and calibration curve (r²) reported >0.99.…”
Section: Lc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many methods have been used to measure spectinomycin and lincomycin in animal-derived foods and animal feedstuffs, including fluorescent latex immunoassay (FLI) [11], micellar electrokinetic capillary chromatography combined with ultraviolet detection (MEKC-UVD) [12], enzyme-linked immunosorbent assay (ELISA) [13], high-performance liquid chromatography with electrochemical detection (HPLC-ECD) [14,15], HPLC with fluorescence detection (FLD) [16], HPLC-UVD [17,18], HPLC with evaporative light-scattering detection (ELSD) [19,20], hydrophilic interaction chromatography with mass spectrometry (HILIC-MS) [21], HILIC tandem MS (MS/MS) [22], HPLC-MS [23], HPLC-MS/MS [24][25][26][27][28], gas chromatography-nitrogen phosphorus detection (GC-NPD) [29,30] and GC-MS [30]. The FLI, ELISA, ECD, FLD, UVD and ELSD methods have low sensitivity, specificity, recovery and precision and have many limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there was a need for matrices in which antibiotics could be detected over a longer time span. For the monitoring of antibiotic use in poultry, the analysis of feathers provided a means to detect antibiotic residues with a long detection window, even after they were excreted fully from muscle and liver (San Martín et al 2007;Cornejo et al 2011b;Berendsen et al 2013;Cornejo et al 2017;Pokrant et al 2018;Církva et al 2019;Maddaleno et al 2019). Using such a noninvasive method, antibiotic use during almost the whole lifespan of a broiler can be monitored, making it possible to better enforce registration of antibiotics use aiming for prudent application (Jansen et al 2016(Jansen et al , 2017.…”
Section: Introductionmentioning
confidence: 99%